Research and design of the protection scheme on bluetooth location privacy - YU Bin; ZHANG Shun (Tongxin xuebao)
The attack mechanism of bluetooth location privacy and the disadvantages of the current protection scheme were analyzed and a model of hierarchical address was established.On the basis of the model,a protection scheme on bluetooth location privacy was designed.Compared with others,this scheme can not only resist eavesdroping,replay attack,frequency hop sequence attack,conversation address tracking attack,dictionary attack and man in the middle attack,but also need little computing and storage.